Implementasi Perkuliahan Keterampilan Berbahasa secara Daring (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
Online lectures demand creativity in all respects for both the teachers and the learners. In lecturing, Indonesian language skills for the collegians in Teacher Education at the Islamic State Islamic School (PGMI) major UIN Sayid Ali Rahmatullah Tulungagung (UIN SATU), especially during the Final Semester Examination (UAS), certain methods are needed so that the main objectives of the lecture can be achieved. At UAS Even of 2020/2021, collegians practice the results of attending Indonesian Language Skills lectures for one semester by teaching the Language Skills to elementary (MI/SD) students who live around their homes. The results of practicing these skills are made in the form of a report. Furthermore, the results of the report are used as a source of data in the form of documents and will be analyzed through the Miles and Huberman model (Sugiyono, 2016). The type of research used in this research is literature study by tracing several references in the library. The data findings will be discussed in accordance with online learning innovations (Harmanto, 2020). The results showed a positive response from parents and students. In addition, there are also several obstacles, including students who do not focus on learning, are not serious, are anxious, and so on.